Assessment of genetic polymorphism in sea buckthorn (Hippophae L.) of different environmentally-geographical origin by ISSR-markers - A. Y. Zemtsova; Y. A. Zubarev; A. V. Gunin; M. S. Ivanova (Вавиловский журнал генетики и селекции)
Sea buckthorn, despite of high popularity at the moment, is not a common object of genetic researches. Some efforts of foreign scientists in this field are concerned with only big systematic groups like species and subspecies. At the same time genetic researches inside of subspecies mongolica growing in Siberia till recently have not been started. There are too many so called ecotypes of sea buckthorn belonging to Hippophae rhamnoides ssp. mongolica growing in different environmentally-geographical areas. That is why the task of deep genetic research of that subspecies is very important. The absence of an approved procedure of genome definition for Siberian sea buckthorn makes the above task quite complicated. That is why the main aim of the current investigation was developing a procedure of ISSR-analysis for sea buckthorn growing in Siberia, as well as preliminary estimation of genetic polymorphism of sea buckthorn varieties belonging to different environmentally-geographical areas by methods of molecular markers. As a result, the procedure of ISSR-analysis for sea buckthorn growing in Siberia has been developed. From 32 estimated ISSR-markers only 6 have been educed as effective for ISSR-locus polymorphism evaluation of sea buckthorn. The annealing temperature for each primer has been found. Analyses of ISSR-markers polymorphism as well as genetic diversity of 17 sea buckthorn varieties have been done. ISSR-spectrum analyses of sea buckthorn plants have educed 56 amplified DNA fragments, 36 of them were polymorphic. According to obtained data a dendrogram of genetic affinity of evaluated varieties has been built, where one variety generates one cluster. In general, it conforms to the idea that one species is divided into subspecies and one subspecies is divided into different ecotypes. As a result of cluster analyses all investigated varieties were divided into two big groups. The first includes varieties belonging to H. rhamnoides ssp. mongolica, H. rhamnoides ssp. rhamnoides, H. rhamnoides ssp. caucasica; the second includes Danube and Yutlandian ecotypes belonging to H. rhamnoides ssp. carpatica. The occurrence of H. rhamnoides ssp. rhamnoides and H. rhamnoides ssp. caucasica inside the first group allows us to make an assumption about their closer genetic relationship with H. rhamnoides ssp. mongolica, which is consistent with their similar morphological features. Revealed ISSR-locus polymorphism as well as the results of clusters analyses allows ISSR-analyses to be recommended for sea buckthorn variability evaluation as well as for genotyping varieties.